Modified nanohollow silicon-carbon composite material and preparation method thereof
Patent Information
- Application Number
- CN202611207818.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-30
AI Technical Summary
现有的硅碳负极材料碳层循环脱落、容量保持率、首次库仑效率和锂离子扩散系数低的问题
1、本发明通过弱碱活化纳米空心硅,使纳米空心硅表面生成大量硅羟基,3-氨丙基三乙氧基硅烷水解后与硅羟基脱水缩合,在纳米空心硅表面通过Si-O-Si共价键接枝氨基有机分子链,得到改性空心硅分散液;纳米空心硅表面构建Si-O-Si有机过渡层,预先钝化硅表面高活性位点,减少硅直接接触电解液;同时Si-O-Si有机过渡层为后续包覆层提供均匀生长基底,减少包覆缺陷;改性纳米空心硅碳复合材料的碳层不再依靠物理吸附附着在硅表面,而是通过共价有机桥梁实现刚性连接,缓解了充放电膨胀导致的包覆层整体脱落,提升了长循环容量保持率。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery anode material technology, specifically to a modified nano-hollow silicon-carbon composite material and its preparation method. Background Technology
[0002] Lithium-ion batteries, with their advantages of high energy density, long cycle life, and no memory effect, are widely used in new energy vehicles, portable electronic devices, and energy storage systems. As terminal devices rapidly iterate towards longer battery life, miniaturization, and higher power, the theoretical capacity of traditional graphite anodes, at only 372 mAh / g, can no longer meet the application requirements of high-energy-density lithium batteries. Silicon-based materials, with their extremely high theoretical specific capacity (4200 mAh / g), low lithium intercalation potential, abundant reserves, and environmental friendliness, are one of the best candidate materials to replace traditional graphite and prepare high-capacity lithium-ion battery anode materials.
[0003] Compared to solid nano-silicon, hollow nano-silicon, with its unique hollow cavity structure, can effectively buffer the nearly 300% volume expansion of silicon during lithium insertion / extraction, alleviating electrode pulverization and cracking problems, and significantly improving the cycle stability of silicon-based anodes. It has become a research hotspot for silicon-carbon anode materials. However, pure hollow nano-silicon materials still have many inherent defects, severely restricting their industrial application: First, silicon has extremely poor intrinsic conductivity, resulting in slow electron transport rates during charging and discharging, leading to poor rate performance and severe polarization. Second, the active sites on the hollow silicon surface are exposed, making it easy for the electrolyte to continuously decompose on the silicon surface, forming an unstable and unevenly thick SEI film that continuously consumes electrolyte and lithium ions, resulting in low initial coulombic efficiency and continuous capacity decay during cycling. Third, a single hollow structure can only alleviate volume deformation and cannot fundamentally solve the problems of silicon shell structure collapse and active material shedding, making it difficult to guarantee the integrity of the electrode structure after long-term cycling.
[0004] Currently, the modification methods for nano-hollow silicon in the industry are relatively limited, mostly employing stepwise modification processes such as single carbon coating, simple element doping, or surface functionalization, which have significant technical shortcomings. Traditional carbon coating is mostly a physical coating mode, where the carbon layer and silicon substrate are only bonded by intermolecular forces. During charge-discharge cycles, carbon layer peeling and shedding can easily occur due to silicon volume deformation, failing to achieve long-term stable protection. Single nitrogen doping and phosphorus doping modification methods can only slightly improve the conductivity of the material and cannot effectively anchor the silicon-based structure or stabilize the electrode interface. On the other hand, stepwise multiple modification processes have problems such as cumbersome operation, high process repeatability, poor interface compatibility, and easy generation of structural defects. Summary of the Invention
[0005] The purpose of this invention is to provide a modified nano-hollow silicon-carbon composite material and its preparation method, thereby solving the following technical problems: Existing silicon-carbon anode materials suffer from problems such as carbon layer shedding during cycling, low capacity retention, low initial coulombic efficiency, and low lithium-ion diffusion coefficient.
[0006] The objective of this invention can be achieved through the following technical solutions: A method for preparing a modified nano-hollow silicon-carbon composite material includes the following steps: Aminated hollow silicon nanoparticles are obtained by amination treatment; then, a TiOP interface anchoring transition layer and a nitrogen-doped porous carbon shell are sequentially coated on the surface of the amination hollow silicon nanoparticles to obtain a modified hollow silicon-carbon composite material.
[0007] As a further embodiment of the present invention, the preparation method of the aminated hollow silicon nanoparticles includes the following steps: under a nitrogen atmosphere, the hollow silicon nanoparticles and an aqueous ethanol solution are added to a reaction flask for dispersion, the pH of the system is adjusted to 9-10, an aminosilane grafting agent is added to the reaction flask, the mixture is stirred at room temperature for 2-2.5 hours, centrifuged, washed, and dried to obtain the aminated hollow silicon nanoparticles.
[0008] As a further aspect of the present invention: the ratio of the nano-hollow silicon, the ethanol aqueous solution, and the aminosilane grafting agent is 0.9-1.1g:72-88mL:0.072-0.088g; the ethanol aqueous solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 4:1; The aminosilane grafting agent is any one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-aminoethyl-3-aminopropylmethyldiethoxysilane, and N-β-aminoethyl-γ-aminopropyltrimethoxysilane.
[0009] As a further aspect of the present invention, the method for preparing the TiOP interface anchoring transition layer includes the following steps: immersing aminated nano-hollow silicon in a titanium-phosphorus composite sol to form a TiOP interface anchoring transition layer on the surface of the nano-hollow silicon.
[0010] As a further aspect of the present invention: the preparation method of the titanium-phosphorus composite sol includes: adding tetrabutyl titanate, an aqueous solution of phosphoric acid and anhydrous ethanol into a beaker and dispersing them to obtain the titanium-phosphorus composite sol; The impregnation process includes the following steps: immersing aminated nano-hollow silicon into a titanium phosphate composite sol, stirring at room temperature for 7.5-8.5 hours, centrifuging, washing, and drying to obtain nano-hollow silicon with a TiOP interface anchoring transition layer coated on the surface.
[0011] As a further aspect of the present invention: the ratio of tetrabutyl titanate, phosphoric acid aqueous solution, and anhydrous ethanol is 0.11-0.13g: 0.049-0.054g: 18-22mL; the concentration of the phosphoric acid aqueous solution is 0.1mol / L; The ratio of the aminated nano-hollow silicon and titanium phosphate composite sol is 0.92-1.13 g: 19-21 mL.
[0012] As a further aspect of the present invention, the preparation method of the nitrogen-doped porous carbon shell includes the following steps: adding nano-hollow silicon with a TiOP interface anchoring transition layer on its surface, resorcinol, formaldehyde solution, CTAB, melamine, polyimide emulsion and ethanol aqueous solution to a reaction flask, stirring at room temperature for 3.5-4.5 h, then transferring the system to a hydrothermal reactor, reacting hydrothermally at 175-185℃ for 5-7 h, washing and drying to obtain composite precursor powder; carbonizing the composite precursor powder at high temperature to obtain a nitrogen-doped porous carbon shell formed on the surface of nano-hollow silicon with a TiOP interface anchoring transition layer on its surface, i.e., modified nano-hollow silicon-carbon composite material.
[0013] As a further aspect of the present invention: the ratio of the amount of nano-hollow silicon with a TiOP interface anchoring transition layer, resorcinol, formaldehyde solution, CTAB, melamine, polyimide emulsion, and ethanol-water solution is 0.94-1.18g: 0.25-0.35g: 0.375-0.525g: 0.125-0.175g: 0.25-0.35g: 2.5-4.0g: 80-120mL; the concentration of the formaldehyde solution is 37wt%; and the concentration of the polyimide emulsion is 8wt%.
[0014] As a further embodiment of the present invention, high-temperature carbonization includes the following steps: placing the composite precursor powder in an argon-protected tube furnace, heating it at 3-5℃ / min to 345-355℃ and holding it at that temperature for 50-70 min, then heating it at 2-3℃ / min to 840-860℃ and holding it at that temperature for 2.5-3.5 h, then naturally cooling it to room temperature, grinding it through a 200-mesh sieve, and obtaining the modified nano-hollow silicon-carbon composite material.
[0015] As a further aspect of the present invention: the method for preparing polyimide emulsion includes the following steps: 4,4'-Diaminodiphenyl ether, N,N-dimethylacetamide, and pyromellitic dianhydride were added to a nitrogen-protected flask, heated to 0-5°C in an ice-water bath, and stirred for 4-6 hours. After returning to room temperature, saturated triethylamine was added to adjust the pH to 7.5-8.0, followed by the addition of an aqueous ethanol solution. The N,N-dimethylacetamide solvent was removed by vacuum distillation, and the mixture was diluted with an aqueous ethanol solution to obtain a polyimide emulsion.
[0016] As a further embodiment of the present invention: the ratio of 4,4'-diaminodiphenyl ether, N,N-dimethylacetamide, and pyromellitic dianhydride is 10g:17-21g:11.1-11.4g.
[0017] A modified nano-hollow silicon-carbon composite material is prepared by the method described above.
[0018] The beneficial effects of this invention are: 1. This invention activates nano-hollow silicon with a weak base, generating a large number of silanol groups on the surface of the nano-hollow silicon. After hydrolysis of 3-aminopropyltriethoxysilane, it undergoes dehydration condensation with the silanol groups, and amino organic molecular chains are grafted onto the surface of the nano-hollow silicon through Si-O-Si covalent bonds to obtain a modified hollow silicon dispersion. A Si-O-Si organic transition layer is constructed on the surface of the nano-hollow silicon to pre-passivate the highly active sites on the silicon surface and reduce direct contact between silicon and electrolyte. At the same time, the Si-O-Si organic transition layer provides a uniform growth substrate for the subsequent coating layer, reducing coating defects. The carbon layer of the modified nano-hollow silicon carbon composite material no longer relies on physical adsorption to adhere to the silicon surface, but achieves rigid connection through covalent organic bridges, which alleviates the overall peeling of the coating layer caused by charge and discharge expansion and improves the long-cycle capacity retention rate.
[0019] 2. This invention utilizes tetrabutyl titanate and phosphoric acid solution to form a titanium-phosphorus composite sol, which, under the coordination of amino sites, condenses with Si-OH grafted layers to construct a TiOP transition thin layer with a Si-O-Ti-P bonded structure on the surface of hollow nano-silicon, resulting in a TiOP-modified composite dispersion. The TiOP transition thin layer in the TiOP-modified composite dispersion densely coats the surface of the hollow nano-silicon, forming a physical barrier that inhibits electrolyte penetration into the silicon core, significantly reducing irreversible side reactions during the initial lithium intercalation stage. The stable interface of the Si-O-Ti-P bonded structure reduces the disordered and continuous growth of the new SEI film, improving… First-time coulombic efficiency; the TiOP transition thin layer possesses suitable mechanical toughness, which can act as a stress buffer layer, dispersing the interfacial stress generated by the volume expansion of the modified hollow silicon-carbon composite material, and preventing the carbon shell from directly bearing huge stress and breaking; the multi-level covalent interface of the modified hollow silicon-carbon composite material ensures that each layer remains electrically connected during the expansion and contraction process, and the conductive path is not interrupted, thus improving the capacity retention rate; at the same time, the TiOP transition thin layer itself has lithium-ion conductivity, eliminating the interfacial impedance barrier between the hollow silicon nanoparticles and the outer carbon layer, allowing lithium ions to migrate rapidly through the chemical bonding interface, thereby improving the lithium-ion diffusion coefficient.
[0020] 3. This invention utilizes gradient nitrogen-doped porous carbon co-assembly, followed by hydrothermal curing and segmented high-temperature argon carbonization, simultaneously completing precursor pyrolysis, TiOP crystallization, and gradient nitrogen-doped porous carbon shell formation to construct a complete multi-level core-shell composite structure, resulting in a modified nano-hollow silicon-carbon composite material. The relatively dense inner carbon shell of the modified nano-hollow silicon-carbon composite material prevents a large amount of electrolyte from invading the core, avoiding the repeated formation of a thick SEI film on the surface of the nano-hollow silicon, thus improving the first coulombic efficiency. The outer porous structure of the modified nano-hollow silicon-carbon composite material reserves a small amount of deformation space, while the dense inner carbon layer maintains structural integrity. The gradient nitrogen-doped carbon has higher mechanical toughness, alleviating particle pulverization during cycling. During cycling, particle integrity is maintained, the conductive network remains connected, reversible capacity decay is slowed down, and capacity retention is significantly improved. Furthermore, the presence of mesoporous channels in the carbon shell shortens the lithium-ion solid-phase diffusion distance, allowing the electrolyte to easily wet the particle interior. These three factors synergistically reduce charge transfer resistance, shorten ion migration paths, and improve the lithium-ion diffusion coefficient. Detailed Implementation
[0021] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0022] In this application, the nano-hollow silicon is selected from Guangzhou Hongwu Materials Technology Co., Ltd., with a particle size of 100-200nm and a purity of ≥99%; In this application, 3-aminopropyltriethoxysilane is selected from Shanghai Aladdin Biochemical Technology Co., Ltd., product number A107147, with a purity ≥99%. Example
[0023] A method for preparing a modified nano-hollow silicon-carbon composite material includes the following steps: S1. Preparation of Aminated Hollow Silicon Nanoparticles Anhydrous ethanol and deionized water were mixed in a volume ratio of 4:1 to prepare an ethanol-water solution. Under a nitrogen atmosphere, 0.9 g of nano-hollow silicon and 72 mL of ethanol aqueous solution were added to a reaction flask for dispersion. The pH of the system was adjusted to 9 with saturated ammonia water and stirred at room temperature for 30 min. Then, 0.072 g of 3-aminopropyltriethoxysilane was added to the flask and stirred for 2 h. After centrifugation, the precipitate was washed three times with anhydrous ethanol and deionized water and dried under vacuum to obtain aminated nano-hollow silicon.
[0024] S2. Preparation of nano-hollow silicon with a TiOP interface anchoring transition layer coated on the surface. 0.11 g of tetrabutyl titanate, 0.049 g of 0.1 mol / L phosphoric acid aqueous solution, and 18 mL of anhydrous ethanol were added to a beaker and dispersed to obtain a titanium-phosphorus composite sol for later use. 0.92 g of aminated hollow silicon nanoparticles were immersed in 19 mL of titanium phosphate composite sol and stirred at room temperature for 7.5 h. After centrifugation, the precipitate was washed three times with anhydrous ethanol and dried to obtain hollow silicon nanoparticles with a TiOP interface anchoring transition layer on the surface.
[0025] S3. Preparation of modified nano-hollow silicon-carbon composite materials 10 g of 4,4'-diaminodiphenyl ether, 17 g of N,N-dimethylacetamide, and 11.1 g of pyromellitic dianhydride were added to a nitrogen-protected flask, heated to 0°C in an ice-water bath, and stirred for 4 h. After returning to room temperature, saturated triethylamine was added to adjust the pH to 7.5, followed by the addition of an aqueous ethanol solution. The N,N-dimethylacetamide solvent was removed by vacuum distillation, and the mixture was diluted with an aqueous ethanol solution to obtain a polyimide emulsion with a solid content of 8 wt%.
[0026] 0.94 g of nano-hollow silicon with a TiOP interfacial anchoring transition layer, 0.25 g of resorcinol, 0.375 g of 37 wt% formaldehyde solution, 0.125 g of CTAB, 0.25 g of melamine, 2.5 g of 8 wt% polyimide emulsion, and 80 mL of ethanol aqueous solution were added to a reaction flask. After stirring at room temperature for 3.5 h, the system was transferred to a hydrothermal reactor and hydrothermally reacted at 175 °C for 5 h. After the hydrothermal reaction was completed, the mixture was cooled to room temperature and the precipitate was collected. The precipitate was washed three times with anhydrous ethanol and deionized water, and then dried to constant weight in a vacuum drying oven at 55 °C to obtain a composite precursor powder. The composite precursor powder was placed in an argon-protected tube furnace and heated to 345 °C at 3 °C / min and held for 50 min, then heated to 840 °C at 2 °C / min and held for 2.5 h. After naturally cooling to room temperature, the mixture was ground through a 200-mesh sieve to obtain the modified nano-hollow silicon-carbon composite material. Example
[0027] A method for preparing a modified nano-hollow silicon-carbon composite material includes the following steps: S1. Preparation of Aminated Hollow Silicon Nanoparticles Anhydrous ethanol and deionized water were mixed in a volume ratio of 4:1 to prepare an ethanol-water solution. Under a nitrogen atmosphere, 1.0 g of nano-hollow silicon and 80 mL of ethanol aqueous solution were added to a reaction flask for dispersion. The pH of the system was adjusted to 9 with saturated ammonia water and stirred at room temperature for 35 min. Then, 0.08 g of 3-aminopropyltriethoxysilane was added to the flask and stirred for 2.3 h. After centrifugation, the precipitate was washed four times with anhydrous ethanol and deionized water and dried under vacuum to obtain aminated nano-hollow silicon.
[0028] S2. Preparation of nano-hollow silicon with a TiOP interface anchoring transition layer coated on the surface. 0.12 g of tetrabutyl titanate, 0.052 g of 0.1 mol / L phosphoric acid aqueous solution, and 20 mL of anhydrous ethanol were added to a beaker and dispersed to obtain a titanium-phosphorus composite sol for later use. 1.1 g of aminated hollow silicon nanoparticles were immersed in 20 mL of titanium phosphate composite sol and stirred at room temperature for 8.0 h. After centrifugation, the precipitate was washed four times with anhydrous ethanol and dried to obtain hollow silicon nanoparticles with a TiOP interface anchoring transition layer on the surface.
[0029] S3. Preparation of modified nano-hollow silicon-carbon composite materials 10 g of 4,4'-diaminodiphenyl ether, 19 g of N,N-dimethylacetamide, and 11.2 g of pyromellitic dianhydride were added to a nitrogen-protected flask, heated to 3°C in an ice-water bath, and stirred for 5 h. After returning to room temperature, saturated triethylamine was added to adjust the pH to 7.7, followed by the addition of an aqueous ethanol solution. The N,N-dimethylacetamide solvent was removed by vacuum distillation, and the mixture was diluted with an aqueous ethanol solution to obtain a polyimide emulsion with a solid content of 8 wt%.
[0030] 1.1 g of nano-hollow silicon with a TiOP interfacial anchoring transition layer, 0.3 g of resorcinol, 0.45 g of 37 wt% formaldehyde solution, 0.15 g of CTAB, 0.3 g of melamine, 3.2 g of 8 wt% polyimide emulsion, and 100 mL of ethanol aqueous solution were added to a reaction flask. After stirring at room temperature for 4 h, the system was transferred to a hydrothermal reactor and hydrothermally reacted at 180 °C for 6 h. After the hydrothermal reaction was completed, the mixture was cooled to room temperature and the precipitate was collected. The precipitate was washed four times with anhydrous ethanol and deionized water, and then dried to constant weight in a vacuum drying oven at 60 °C to obtain composite precursor powder. The composite precursor powder was placed in an argon-protected tube furnace and heated to 350 °C at 4 °C / min and held for 60 min, then heated to 850 °C at 2 °C / min and held for 3 h. After naturally cooling to room temperature, the mixture was ground through a 200-mesh sieve to obtain the modified nano-hollow silicon-carbon composite material. Example
[0031] A method for preparing a modified nano-hollow silicon-carbon composite material includes the following steps: S1. Preparation of Aminated Hollow Silicon Nanoparticles Anhydrous ethanol and deionized water were mixed in a volume ratio of 4:1 to prepare an ethanol-water solution. Under a nitrogen atmosphere, 1.1 g of nano-hollow silicon and 88 mL of ethanol aqueous solution were added to a reaction flask for dispersion. The pH of the system was adjusted to 10 with saturated ammonia water and stirred at room temperature for 40 min. Then, 0.088 g of 3-aminopropyltriethoxysilane was added to the flask and stirred for 2.5 h. After centrifugation, the precipitate was washed 3-5 times with anhydrous ethanol and deionized water and dried under vacuum to obtain aminated nano-hollow silicon.
[0032] S2. Preparation of nano-hollow silicon with a TiOP interface anchoring transition layer coated on the surface. 0.13 g of tetrabutyl titanate was added to a beaker and dispersed with 0.054 g of 0.1 mol / L phosphoric acid aqueous solution and 22 mL of anhydrous ethanol to obtain a titanium-phosphorus composite sol for later use. 1.13 g of aminated hollow silicon nanoparticles were immersed in 21 mL of titanium phosphate composite sol and stirred at room temperature for 7.5 h. After centrifugation, the precipitate was washed five times with anhydrous ethanol and dried to obtain hollow silicon nanoparticles with a TiOP interface anchoring transition layer on the surface.
[0033] S3. Preparation of modified nano-hollow silicon-carbon composite materials 10 g of 4,4'-diaminodiphenyl ether, 21 g of N,N-dimethylacetamide, and 11.4 g of pyromellitic dianhydride were added to a nitrogen-protected flask, heated to 5°C in an ice-water bath, and stirred for 6 h. After returning to room temperature, saturated triethylamine was added to adjust the pH to 8.0, followed by the addition of an aqueous ethanol solution. The N,N-dimethylacetamide solvent was removed by vacuum distillation, and the mixture was diluted with an aqueous ethanol solution to obtain a polyimide emulsion with a solid content of 8 wt%.
[0034] 1.18 g of nano-hollow silicon with a TiOP interfacial anchoring transition layer, 0.35 g of resorcinol, 0.525 g of 37 wt% formaldehyde solution, 0.175 g of CTAB, 0.35 g of melamine, 4.0 g of 8 wt% polyimide emulsion, and 120 mL of ethanol aqueous solution were added to a reaction flask. After stirring at room temperature for 4.5 h, the system was transferred to a hydrothermal reactor and hydrothermally reacted at 185 °C for 7 h. After the hydrothermal reaction was completed, the mixture was cooled to room temperature and the precipitate was collected. The precipitate was washed five times with anhydrous ethanol and deionized water, and then dried to constant weight in a vacuum drying oven at 65 °C to obtain composite precursor powder. The composite precursor powder was placed in an argon-protected tube furnace and heated to 355 °C at 5 °C / min and held for 70 min, then heated to 860 °C at 3 °C / min and held for 3.5 h, and then naturally cooled to room temperature. The mixture was then ground through a 200-mesh sieve to obtain the modified nano-hollow silicon-carbon composite material.
[0035] Comparative Example 1 Compared with Example 3, this comparative example omits steps S1, S2 and S3, and directly uses the nano-hollow silicon from step S1 for the silicon-carbon anode, while the remaining components are exactly the same.
[0036] Comparative Example 2 Compared with Example 3, step S2 was omitted in this comparative example, and the modified hollow silica dispersion prepared in step S1 was used to replace the TiOP modified composite dispersion in step S3. All other components were exactly the same.
[0037] Comparative Example 3 Compared with Example 3, in step S3, melamine and polyimide emulsion were not added to this comparative example, but the other components were exactly the same.
[0038] Performance testing The modified nano-hollow silicon-carbon composite anode materials prepared in Examples 1-3 and Comparative Examples 1-3 were used to prepare anode sheets, which were then assembled into lithium-ion batteries. The performance of each battery group was tested. The preparation methods of the anode sheets and lithium-ion batteries include the following steps: A negative electrode slurry is prepared by mixing 94-97% negative electrode material, 0.1-1% conductive agent (single-walled carbon nanotubes), and 3-5% binder (PAALi) in a mass ratio, adding a certain amount of high-purity water, coating it onto copper foil, drying it in a vacuum drying oven at 110℃ for 10 hours, and then rolling and punching it to obtain the negative electrode sheet. A lithium sheet is used as the counter electrode, and 1.0 mol / L LiPF6 / EC:DEC=1:1 Vol% +5% FEC is used as the electrolyte. The cells are assembled into coin cells in a glove box under an argon atmosphere.
[0039] The capacity retention rate and initial coulombic efficiency of coin cells after 100 cycles were determined in accordance with the standard GB / T 44027.1-2024 "Determination Methods for Carbon Materials - Part 1: Determination of Initial Discharge Specific Capacity, Initial Coulombic Efficiency and Capacity Retention Rate at Different Discharge Rates". The lithium-ion diffusion coefficient of silicon-carbon anode materials was determined in accordance with the standard SJ / T 12060-2025 "Test Method for Lithium-ion Diffusion Coefficient of Lithium-ion Battery Materials".
[0040] The test results are shown in the table below:
[0041] As shown in the table above, the modified hollow silicon-carbon composite material prepared in this application exhibits high capacity retention, first-pass coulombic efficiency, and lithium-ion diffusion coefficient when used in silicon-carbon anode materials. Compared with Comparative Example 1, Examples 1-3 show that Comparative Example 1 lacks a covalent graft layer, TiOP transition layer, and carbon shell, resulting in direct contact between the hollow silicon nanoparticles and the electrolyte. The severe volume expansion during lithium insertion / extraction causes particle pulverization, conductive network breakage, and continuous side reactions. In Example 3, the modified hollow silicon-carbon composite material relies on a multi-level covalent coating structure to passivate the surface of the hollow silicon nanoparticles, buffer volume deformation, and suppress irreversible SEI film retention. The continuous growth process results in higher initial coulombic efficiency, capacity retention, and lithium-ion diffusion coefficient. Compared to Comparative Example 2, in Examples 1-3, a TiOP nano-transition layer is generated in situ between the hollow silicon shell and the carbon layer, forming a Si-O-Ti-P chemical bond-locked structure that strongly constrains silicon expansion while improving cycle stability. Compared to Comparative Example 3, the modified hollow silicon-carbon composite material has a gradient nitrogen-doped carbon shell with a dense inner layer and a porous outer layer, which balances electrolyte barrier, structural protection, and rapid lithium-ion transport, thereby improving the overall capacity retention, initial coulombic efficiency, and lithium-ion diffusion coefficient.
[0042] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.
Claims
1. A method for preparing a modified nano-hollow silicon-carbon composite material, characterized in that, Includes the following steps: Aminated hollow silicon nanoparticles were obtained by amination treatment. Then, a TiOP interface anchoring transition layer and a nitrogen-doped porous carbon shell are sequentially coated onto the surface of the aminated nano-hollow silicon to obtain a modified nano-hollow silicon-carbon composite material.
2. The method for preparing a modified nano-hollow silicon-carbon composite material according to claim 1, characterized in that, The preparation method of the aminated hollow silicon nanoparticles includes the following steps: under a nitrogen atmosphere, the hollow silicon nanoparticles and an aqueous ethanol solution are added to a reaction flask for dispersion, the pH of the system is adjusted to 9-10, an aminosilane grafting agent is added to the reaction flask, the mixture is stirred at room temperature for 2-2.5 hours, centrifuged, washed, and dried to obtain the aminated hollow silicon nanoparticles.
3. The method for preparing a modified nano-hollow silicon-carbon composite material according to claim 2, characterized in that, The ratio of the nano-hollow silicon, the ethanol aqueous solution, and the aminosilane grafting agent is 0.9-1.1g:72-88mL:0.072-0.088g; the ethanol aqueous solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 4:
1. The aminosilane grafting agent is any one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-aminoethyl-3-aminopropylmethyldiethoxysilane, and N-β-aminoethyl-γ-aminopropyltrimethoxysilane.
4. The method for preparing a modified nano-hollow silicon-carbon composite material according to claim 1, characterized in that, The method for preparing the TiOP interface anchoring transition layer includes the following steps: immersing aminated nano-hollow silicon in a titanium-phosphorus composite sol to form a TiOP interface anchoring transition layer on the surface of the nano-hollow silicon.
5. The method for preparing a modified nano-hollow silicon-carbon composite material according to claim 4, characterized in that, The preparation method of the titanium-phosphorus composite sol includes: adding tetrabutyl titanate, phosphoric acid aqueous solution and anhydrous ethanol into a beaker and dispersing them to obtain titanium-phosphorus composite sol; The impregnation process includes the following steps: immersing aminated nano-hollow silicon into a titanium phosphate composite sol, stirring at room temperature for 7.5-8.5 hours, centrifuging, washing, and drying to obtain nano-hollow silicon with a TiOP interface anchoring transition layer coated on the surface.
6. The method for preparing a modified nano-hollow silicon-carbon composite material according to claim 5, characterized in that, The ratio of tetrabutyl titanate, phosphoric acid aqueous solution, and anhydrous ethanol is 0.11-0.13 g : 0.049-0.054 g : 18-22 mL; the concentration of the phosphoric acid aqueous solution is 0.1 mol / L. The ratio of the aminated nano-hollow silicon and titanium phosphate composite sol is 0.92-1.13 g: 19-21 mL.
7. The method for preparing a modified nano-hollow silicon-carbon composite material according to claim 5, characterized in that, The preparation method of the nitrogen-doped porous carbon shell includes the following steps: adding nano-hollow silicon with a TiOP interface anchoring transition layer on the surface, resorcinol, formaldehyde solution, CTAB, melamine, polyimide emulsion and ethanol aqueous solution to a reaction flask, stirring at room temperature for 3.5-4.5 h, then transferring the system to a hydrothermal reactor, reacting hydrothermally at 175-185℃ for 5-7 h, washing and drying to obtain composite precursor powder; carbonizing the composite precursor powder at high temperature to obtain a nitrogen-doped porous carbon shell formed on the surface of nano-hollow silicon with a TiOP interface anchoring transition layer, i.e., modified nano-hollow silicon-carbon composite material.
8. The method for preparing a modified nano-hollow silicon-carbon composite material according to claim 7, characterized in that, The ratio of the following components to be used is 0.94-1.18g:0.25-0.35g:0.375-0.525g:0.125-0.175g:0.25-0.35g:2.5-4.0g:80-120mL; the concentration of the formaldehyde solution is 37wt%; and the concentration of the polyimide emulsion is 8wt%.
9. The method for preparing a modified nano-hollow silicon-carbon composite material according to claim 7, characterized in that, High-temperature carbonization includes the following steps: placing the composite precursor powder in an argon-protected tube furnace, heating it at 3-5℃ / min to 345-355℃ and holding it at that temperature for 50-70 min, then heating it at 2-3℃ / min to 840-860℃ and holding it at that temperature for 2.5-3.5 h, then naturally cooling it to room temperature, grinding it through a 200-mesh sieve to obtain the modified nano-hollow silicon-carbon composite material.
10. A modified nano-hollow silicon-carbon composite material, characterized in that, It is prepared by the method described in any one of claims 1-9.
